2002
DOI: 10.1111/j.1524-475x.2002.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Dissemination and Utilization of Research for Health‐Care Policy and Practice

Abstract: Volume 9November 18, 2002 Document Number 7 Purpose(1) The purpose of this paper is to construct a comprehensive framework of research dissemination and utilization that is useful for both health policy and clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
199
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(208 citation statements)
references
References 56 publications
(21 reference statements)
3
199
0
3
Order By: Relevance
“…Organizational factors such as culture, decision making, and capacity for EIDM are associated with research use [31]. Therefore, an important role component for KBs involves facilitating organizational change so as to promote a culture conducive to EIDM.…”
Section: Promoting Organizational Changementioning
confidence: 99%
“…Organizational factors such as culture, decision making, and capacity for EIDM are associated with research use [31]. Therefore, an important role component for KBs involves facilitating organizational change so as to promote a culture conducive to EIDM.…”
Section: Promoting Organizational Changementioning
confidence: 99%
“…system-level components, such as the structural, infrastructural, regulatory, political and socio-historical context of the existing healthcare system, are largely absent (Berwick 2003;davis et al 2003;Graham et al 2006;Grol and Grimshaw 1999;Helfrich et al 2007;Jacobson et al 2003;Kitson et al 1998Kitson et al , 2008Lavis et al 2003;stetler 2003;Ward et al 2009), or recognized but given scant description (dobbins et al 2002;Greenhalgh et al 2004), in much of the theoretical work in the knowledge-to-practice literature. findings from this study demonstrated that certain features of the healthcare system -its delivery and support structure, IT infrastructure, policy environment and history of limited collaboration and weak working relationships across organizations -were problematic in the context of sRT implementation.…”
Section: Discussionmentioning
confidence: 99%
“…16 Collaboration between community networks, regulations and legislation, peer pressure and competition are the key environmental factors for successful translation of an innovation from idea into practice. 17 Collaboration among stakeholders is an important facilitator of innovation adoption. 17 Additionally, an organization's social role, formal and informal, influences the effectiveness of implementation.…”
Section: Organization/external Environmentmentioning
confidence: 99%